Application of Differentiated Instruction on Early Childhood Socio-Emotional Development at Tunas Muda Kindergarten, Perhentian Sungka - Tanjung, MHD Agussalim; Sunimaryanti, Sunimaryanti; Andre, Lesis; Sari, Ayu Mustika (The Future of Education Journal, 2025)
This study was motivated by the absence of learning methods that accommodate diverse child growth and development, as well as the low level of social-emotional development at TK Tunas Muda Perhentian Sungkai. Therefore, the research examines the implementation of differentiated learning on children’s social-emotional development. The objective of this research is to explore how differentiated learning supports early childhood social-emotional development.This descriptive qualitative research was conducted at TK Tunas Muda Perhentian Sungkai from March to April 2025 under the theme “I Love the Earth,” with the sub-theme “Caring for Allah’s Creation Plants,” over three sessions. Data were collected through observation, interviews, and documentation, using both primary and secondary data sources. Data analysis included reduction, presentation, and conclusion drawing, while data validity was ensured through triangulation.The findings indicate that differentiated learning at TK Tunas Muda Perhentian Sungkai effectively supports children’s social-emotional development by applying strategies tailored to their needs and creating a supportive learning environment. The percentage of children in the "Developing as Expected" (BSH) category increased from 37.78% to 80%, while those in the "Starting to Develop" (MB) category decreased from 62.22% to 20%, demonstrating the method’s effectiveness. The successful implementation of differentiated learning is supported by teachers, the principal, parents, and available facilities, despite challenges such as limited time, classroom space, varied child characteristics, and learning resources. Collaboration among all parties significantly enhances children's social-emotional development.